Pengembangan Sistem Penentuan Prioritas Kebutuhan Perangkat Lunak Dengan Metode MVGB (Majority Voting Goal Based) - Fikri Arroisi; Bayu Priyambadha; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Requirement engineering is the initial stages of software engineering activities, where requirements elicited and analyzed. Requirement prioritization is an important process in requirement engineering that can determine the success of a software development project. Requirement prioritization activities can choose which requirements are important and less important, so the resource of the development team can focus on solving the key problem first so that resources are not wasted to solve a less urgent problem. MVGB (Majority Voting Goal Based) is a requirements prioritization method that takes into account the value given by each stakeholder as well as the dependency value of a requirement. This system of prioritizing software requirements using MVGB method is a system that provides a place to elicit and prioritize requirements by involving selected stakeholders using web technologies. The system has 46 functional requirements that are useful for elicitation, observation, and prioritization of requirements, the system has been tested with unit testing for 3 major system functions, integration testing for 3 pairs of system main classes, and validation testing for all requirements, the test yield a valid value for all test cases.